Protection off Bird off Paradise Wildlife From Extinction Due to Poaching - Wospakrik, Decky DA (Dinasti Research, 2025)
The hunting of wild birds of paradise results in a decrease in population and damages the ecosystem that has been created by nature. The increase in the hunting of birds of paradise continues to rise year after year, indicating that wildlife protection regulations have not yet effectively and strictly enforced and provided benefits such as a deterrent effect. On the other hand, the development of wildlife trade models follows the advancement of digital technology, namely social media, where wildlife trade no longer recognizes national borders. Thus, changes in regulations and increased multi-sector cooperation between state institutions, NGOs, and international organizations are necessary to enhance law enforcement against the poaching of birds of paradise. This research discusses the protection of birds of paradise from extinction caused by wildlife hunting. This research uses a normative research method with a regulatory approach. The results of this study show that the hunting of wild animals continues to increase year by year, as well as the development and changes in the methods of marketing wild animal hunting results. Therefore, amendments to Law No. 5 of 1990 on the Conservation of Natural Resources and Ecosystems can be made in accordance with technological advancements and to enhance cooperation among state institutions, NGOs, and international relations in law enforcement.